The Impact of Using the Software on Management of Supply Chain Activities in Economic Enterprises According the Point of View of EmployeesField Study: Group of Economic Enterprises in M’sila - Algeria. - Farouk, Herizi; Abdenour, Debbi (The Arab Journal of Administration, 2022)
This study aims to know the role of using software on management of supply chain activities in economic institutions. Furthermore, in order to examine this impact we divided our dependent variable into five main dimensions that are: purchasing activity; stock activity، production activity, distribution activity, and transportation activity. Therefore The field of study was done on four economic institutions in the M’sila’s wilaya that are: Lafarge Holcim, Moulin El-Hodna, Eatit and Maghrep Pipe; we relied on a quantitative study, we used the questionnaire as a main research tool for collection and analysis of data and information. This study was applied on a random sample consist 73 managers and employees. The data was analyzed by using the SPSS V.25 program. Finally, the results of study showed that the degree of use the software in institutions was considerable, but in varying degrees; and there is an impact of using software on management of supply chain activities.